2020
DOI: 10.1080/03079457.2020.1712328
|View full text |Cite
|
Sign up to set email alerts
|

Histologically validated scoring system for the assessment of hock burn in broilers

Abstract: The assessment of bird-based welfare indicators plays an important role in the evaluation of bird welfare. The aim of the study was to histologically validate a visual scoring system for hock burn in broilers and to detect threshold values of a visual score to define welfarerelevant alterations in terms of mild lesions or ulcers of the hock. We collected 200 hocks of 39-to 42-day-old Ross 308 broilers after the slaughter process. Each hock was scored visually ("macro scores" 0-4) and evaluated histologically (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Some welfare issues, like hock burns or skin injuries, present at a low extent in Sasso, were not observed in Green-legged Partridges at all. High body weight of broilers is a known risk factor for the occurrence of hock burns ( Louton et al., 2020 ). In addition to the plumage, injurious pecking may also be directed toward the skin ( Riber and Hinrichsen, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some welfare issues, like hock burns or skin injuries, present at a low extent in Sasso, were not observed in Green-legged Partridges at all. High body weight of broilers is a known risk factor for the occurrence of hock burns ( Louton et al., 2020 ). In addition to the plumage, injurious pecking may also be directed toward the skin ( Riber and Hinrichsen, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There could be an important correlation between macro and micro scores of foot pad in broiler raised in different floor system (Louton et al, 2020). Martins et al (2016) showed that the lesion scores assigned were compatible with the histopathological results, showing that the higher the score, the more severe were the dermal and epidermal lesions.…”
Section: Discussionmentioning
confidence: 62%
“…The depth and width of the lesions can be different, and no lesions can be seen on the soles of the feet after slaughter (Kristensen et al, 2007;Michel et al, 2012). Histological features of the lesions can be an efficient way of determining lesion severity and it would be beneficial to improve the reliability of the scoring systems in terms of animal welfare (Louton et al, 2020). This study was carried out to reveal the histopathological conditions of footpad lesions of broiler occurred into different floor housing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the principals described by Welfare-Quality® (2009) and Louton et al (2020) and the characteristics about the intensity and coloration of the contact lesions at the tibiotarsal region, the lesions were allocated in four different grades: the control group (GC) the articulation without visual alteration; Grade 1 (G1), refers to the joint with mild scarification and pink or reddish color (erythema); Grade 2 (G2), refers to the joint with moderate scarification, crust formation and brownish coloration; Grade 3(G3) refers to the articulation with scarification of severe intensity, presence of crust, ulceration and/or brownish and/or purplish and/or blackish coloration (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was used a total of 942 (CG = 234, G1 = 236, G2 = 235 and G3 = 237) pictures of tibiotarsal region observed in the post-mortem inspection line to perform macroscopic classification. The grading methods was based on the principals described by Welfare-Quality® ( 2009) and Louton et al (2020), utilizing fewer lesion grades (three instead of four) that were created based on characteristics such as intensity and color of the contact lesion in the tibiotarsal region and the presence or absence of scarification.…”
Section: Visual Classificationmentioning
confidence: 99%